Digital Transformation in Population Administration Services: Evaluating the Akudicari Application through Good Governance Principles - Yolanda, Agnes Yosi; Wirantari, I Dewa Ayu Putri (Socio-political Communication and Policy Review, 2025)
This study investigates the digital transformation of population administration services in Indonesia, with a particular focus on the implementation of the Akudicari application at the Department of Population and Civil Registration (Disdukcapil) in Badung Regency, Bali. Population administration services, including the issuance of identity cards, family cards, and birth certificates, are fundamental to ensuring citizens’ legal identity and access to education, health, and social welfare. However, these services have long been constrained by bureaucratic inefficiencies, lengthy procedures, and the persistent problem of service brokerage. The emergence of information and communication technology (ICT) provides new opportunities to overcome these challenges through digital innovation. Akudicari, launched in 2022, represents a local government initiative to enhance efficiency and accountability by allowing citizens to track the progress of their documents online in real time. The study applies a qualitative descriptive method, utilizing interviews, observations, and document analysis to evaluate Akudicari in relation to the principles of good governance—transparency, accountability, efficiency, responsiveness, and public participation. The findings indicate that Akudicari has significantly improved service effectiveness by reducing processing time by nearly 30 percent, providing transparency through open access to real-time information, and minimizing the role of intermediaries in administrative procedures. At the same time, challenges persist, particularly in rural areas, where digital literacy remains low and internet connectivity is inconsistent. Disparities in the digital competencies of civil servants also hinder the optimal use of the application. The study concludes that Akudicari is not only a technological innovation but also an instrument of governance reform that strengthens the relationship between government and citizens. However, its long-term sustainability requires continuous system upgrades, regular staff training, and inclusive community outreach. By addressing these challenges, Akudicari can serve as a scalable model for digital public service delivery in other regions of Indonesia and contribute to global discussions on e-government transformation.